2017
DOI: 10.1002/chir.22685
|View full text |Cite
|
Sign up to set email alerts
|

Intraband optical activity of semiconductor nanocrystals

Abstract: Here we review our three recently developed analytical models describing the intraband optical activity of semiconductor nanocrystals, which is induced by screw dislocations, ionic impurities, or irregularities of the nanocrystal surface. The models predict that semiconductor nanocrystals can exhibit strong optical activity upon intraband transitions and have large dissymmetry of magnetic-dipole absorption. The developed models can be used to interpret experimental circular dichroism spectra of nanocrystals an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Chiral core–shell quantum nanocrystals (NCs), such as chiral CdSe/CdS and CdSe/ZnS with enhanced photoluminescence quantum yields (PLQYs) and environmental stabilities, have recently become an emerging topic of interest because of their promising applications in chiral recognition, stereoselective synthesis, , biosensing, display devices, and so forth. Chiral core–shell quantum NCs also provide an ideal platform for exploring the mechanisms underlying the chirogenesis of excitonic circular dichroism (CD) and the possibility for controlling circularly polarized luminescence (CPL) through the extensive tunability of the size-dependent fluorescence properties as a result of quantum confinement effects. , Three mechanisms for explaining the induction of chirality in chiral metal nanoparticles , (NPs) are often extended to semiconductor NCs: , (i) intrinsically chiral NCs with dislocations and defects, , (ii) ligand-induced chiral surfaces in QDs , or chiral interactions between chiral ligands and achiral QDs, ,, and (iii) achiral QD-based chiral assemblies. Among these mechanisms, ligand exchange with chiral molecules produces tremendous advances in obtaining QDs with a uniform size distribution and providing diverse choices for designing the surface chemistry of QDs to impart chemical properties. To date, an extensive body of experiments and theoretical calculations have been reported toward discovering the origin and modulating the intensity of chirality with various parameters, including the surface ligand motif , (thiolated or nonthiolated, , number of stereocenters, , and surface ligand conformation when bound to QDs) and chemistry of the QDs, namely, the size and shell thickness of the QDs. , Ferry’s work, for instance, compared carboxylate-bound and thiolate-bound chiral CdSe QDs and showed that chiral carboxylic acids can exhibit int...…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chiral core–shell quantum nanocrystals (NCs), such as chiral CdSe/CdS and CdSe/ZnS with enhanced photoluminescence quantum yields (PLQYs) and environmental stabilities, have recently become an emerging topic of interest because of their promising applications in chiral recognition, stereoselective synthesis, , biosensing, display devices, and so forth. Chiral core–shell quantum NCs also provide an ideal platform for exploring the mechanisms underlying the chirogenesis of excitonic circular dichroism (CD) and the possibility for controlling circularly polarized luminescence (CPL) through the extensive tunability of the size-dependent fluorescence properties as a result of quantum confinement effects. , Three mechanisms for explaining the induction of chirality in chiral metal nanoparticles , (NPs) are often extended to semiconductor NCs: , (i) intrinsically chiral NCs with dislocations and defects, , (ii) ligand-induced chiral surfaces in QDs , or chiral interactions between chiral ligands and achiral QDs, ,, and (iii) achiral QD-based chiral assemblies. Among these mechanisms, ligand exchange with chiral molecules produces tremendous advances in obtaining QDs with a uniform size distribution and providing diverse choices for designing the surface chemistry of QDs to impart chemical properties. To date, an extensive body of experiments and theoretical calculations have been reported toward discovering the origin and modulating the intensity of chirality with various parameters, including the surface ligand motif , (thiolated or nonthiolated, , number of stereocenters, , and surface ligand conformation when bound to QDs) and chemistry of the QDs, namely, the size and shell thickness of the QDs. , Ferry’s work, for instance, compared carboxylate-bound and thiolate-bound chiral CdSe QDs and showed that chiral carboxylic acids can exhibit int...…”
mentioning
confidence: 99%
“…31−37 Among these mechanisms, ligand exchange with chiral molecules produces tremendous advances in obtaining QDs with a uniform size distribution and providing diverse choices for designing the surface chemistry of QDs to impart chemical properties. To date, an extensive body of experiments and theoretical calculations have been reported toward discovering the origin and modulating the intensity of chirality with various parameters, including the surface ligand motif 38,39 (thiolated or nonthiolated, 40,41 number of stereocenters, 42,43 and surface ligand conformation 44 when bound to QDs) and chemistry of the QDs, namely, the size and shell thickness of the QDs. 15,45 Ferry's work, 43 for instance, compared carboxylatebound and thiolate-bound chiral CdSe QDs and showed that chiral carboxylic acids can exhibit intense CD signals with anisotropic g CD factors 46 of up to 7.0 × 10 −4 , where g CD = Δε/ε, and Δε is the absorptivity difference between left-and righthanded circularly polarized light.…”
mentioning
confidence: 99%
“…Chiral semiconductor nanocrystals or quantum dots (QDs) are emerging materials with widespread potential applications, including as biological sensors, in document security and anticounterfeiting materials, , in photonics, and in spin-polarized devices. Since their initial preparation by Moloney and co-workers in 2007, where chiral ligands were used as stabilizers in the microwave synthesis of CdS QDs, chirality has been shown to originate from the semiconductor nanocrystal core in the presence of dislocations and defects, from interactions between chiral ligands and the nanocrystal, and from the incorporation and arrangement of nanocrystals into chiral superstructures . Among these, the induction of chirality through postsynthetic ligand exchange, in which chiral ligands replace native achiral ligands on the surface, promises a large design space for tailored and tunable chiral semiconductor nanocrystals. , The nanocrystals can be designed and synthesized independently from the ligands, while subtle differences in the binding of the chiral ligand to the semiconductor nanocrystal influence the circular dichroism (CD) spectra .…”
mentioning
confidence: 99%
“…Metamaterials that display high circular dichroism (CD) are fundamentally important and are also of practical interest. In recent years, there has been a high demand for chiral metamaterials in various fields, including optics, display, and sensing, because of their strong light–matter interaction . Based on their unique optical properties and delicate structure, chiral metamaterials have extended the ability to manipulate light to the realization of negative refractive index, control of angular momentum of light, holographic displays, and chiral sensing .…”
Section: Introductionmentioning
confidence: 99%